Heavy ion beam probing—diagnostics to study potential and turbulence in toroidal plasmas. (10th March 2017) - Melnikov, A.V.; Krupnik, L.I.; Eliseev, L.G.; Barcala, J.M.; Bravo, A.; Chmyga, A.A.; Deshko, G.N.; Drabinskij, M.A.; Hidalgo, C.; Khabanov, P.O.; Khrebtov, S.M.; Kharchev, N.K.; et al.
Abstract: Heavy ion beam probing (HIBP) is a unique diagnostics to study the core plasma potential and turbulence. Advanced HIBPs operate in the T-10 tokamak and TJ-II flexible heliac with fine focused (<1 cm) and intense (100 µ A) beams. They provide measurements in the wide density interval n ¯ e   =  (0.3–5)  ×  10 19 m −3, in a wide range of Ohmic and electron cyclotron resonance heated (ECRH) discharges with various currents at T-10, and in the wide range of magnetic configurations with ECR and neutral beam injection (NBI) heating at TJ-II. Time evolution of the radial profiles and/or local values of plasma parameters from high field side (HFS) to low field side (LFS), −1  <   ρ   <  1, is observed in TJ-II by 125 keV Cs + ions in a single shot, while LFS (+0.2  <   ρ   <  1) is observed in T-10 by 300 keV Tl + ions. Multi-slit energy analyzers provide simultaneously data on the plasma potential ϕ (by the beam extra energy), plasma density n e (by the beam current), poloidal magnetic field B pol (by the beam toroidal shift), poloidal electric filed E pol that allows one to derive the electrostatic turbulent particle flux ΓE×B . The cross-phase of density oscillations produces the phase velocity of their poloidal propagation or rotation; also it gives the poloidal mode number. Dual HIBP, consisting of two identical HIBPs located ¼ torus apart provide the long-range correlations of core plasma parameters. Low-noise high-gain electronics allows us to study broadband turbulence and quasi-coherent modes like geodesic acoustic modes and Alfvén eigenmodes.